In Silico Study on Interaction and Preliminary Toxicity Prediction of Eleutherine americana Components as an Antifungal and Antitoxoplasmosis Candidate - Sophi Damayanti; Nadiyah Athifah Salim Martak; Benny Permana; Adi Suwandi; Rika Hartati; Indra Wibowo (Universitas Gadjah Mada, 2020)
Red bulbs of Eleutherine americana (Aubl.) Merr. ex K. Heyne has been known for its high content of naphthoquinones that have antifungal and antiparasitic activities. In this research, in silico interaction study was performed between 31 compounds reported to be found in E. americana with the selected target proteins for antifungal and antitoxoplasmosis activity using the molecular docking method. An ORPs (OSBP-related proteins), Osh4 (PDB ID: 1ZHX), and N-myristoyltransferase (Nmt, PDB ID: 1IYL) were used as the antifungal target proteins. Toxoplasma gondii purine nucleoside phosphorylase (TgPNP, PDB ID: 3MB8) and calcium-dependent protein kinase-1 (TgCDPK1, PDB ID: 4M84) were used as antitoxoplasmosis target proteins. Three-dimensional structures of the test compounds were made and optimized using GaussView 6.0 and Gaussian 09W. The target proteins were prepared using the Discovery Studio 2016 Program. Aquatic toxicity prediction as the preliminary assessment of the safety of the compounds was performed using ECOSAR v2.0. The results suggest that the compound having both the smallest free binding energy compared with positive control and other test compounds and low predicted toxicity is β-sitosterol with a free binding energy of ‒11.55 and ‒11.18 kcal/mol towards Osh4 and Nmt and ‒8.06 and ‒10.29 kcal/mol towards TgPNP and TgCDPK1, respectively.